Assessing Gaps between Perception and Implementation of Higher Order Thinking Skills (HOTS) in Islamic Higher Education - Muttaqin, Sabilil; Krisnawati, Nofi Maria; Maftuhah, Maftuhah; Syam, Mu’arif; Mustolihudin, Mustolihudin (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2025)
AbstractHigh-order thinking skills (HOTS) is one of the key competencies in 21st-century education that requires students to be able to think critically, creatively, and solve complex problems. This study aims to assess lecturers' understanding, perceptions, and practices in implementing HOTS-based learning and evaluation in private Islamic higher education institutions (PTKIS) in the KOPERTAIS region I (DKI Jakarta and Banten). This study employed qualitative method with a case study approach. This research utilized two data collection techniques, namely open-ended questionnaires based on Google Forms and document analysis obtained through Semester Learning Plans (RPS) and learning outcome evaluation instruments. The participants in this study were 13 lecturers from PTKIS in the Kopertais region I that were garnered through snowball sampling. The findings of this study uncovered three main areas: lecturers’ understanding of HOTS concepts, implementation of HOTS in teaching, and the relevance of evaluation instruments to HOTS. Based on these three categories, the findings suggest that some lecturers have a good understanding of HOTS concepts, but there are also some who are unable to effectively apply these concepts in teaching and developing HOTS-based evaluation instruments. This study also signifies the importance of aligning the understanding, implementation, and the development of HOTS-based instruments to create high-quality learning. AbstrakKeterampilan berpikir tingkat tinggi (Higher Order Thinking Skills/HOTS) merupakan salah satu kompetensi kunci dalam pendidikan abad ke-21 yang menuntut peserta didik untuk mampu berpikir kritis, kreatif, dan memecahkan masalah kompleks. Penelitian ini bertujuan untuk menilai pemahaman, persepsi, dan praktik dosen dalam mengimplementasikan pembelajaran dan evaluasi berbasis HOTS di Perguruan Tinggi Keagamaan Islam Swasta (PTKIS) wilayah KOPERTAIS I (DKI Jakarta dan Banten). Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus. Teknik pengumpulan data yang digunakan meliputi kuesioner terbuka berbasis Google Forms dan analisis dokumen yang diperoleh dari Rencana Pembelajaran Semester (RPS) serta instrumen evaluasi hasil belajar. Partisipan dalam penelitian ini adalah 13 dosen PTKIS di wilayah Kopertais I yang dipilih melalui teknik snowball sampling. Temuan penelitian ini mengungkapkan tiga fokus utama: pemahaman dosen terhadap konsep HOTS, implementasi HOTS dalam pengajaran, dan relevansi instrumen evaluasi terhadap HOTS. Berdasarkan ketiga kategori tersebut, hasil penelitian menunjukkan bahwa sebagian dosen memiliki pemahaman yang baik tentang konsep HOTS, namun masih ada yang belum mampu menerapkan konsep tersebut secara efektif dalam pengajaran maupun pengembangan instrumen evaluasi berbasis HOTS. Studi ini juga menegaskan pentingnya penyelarasan antara pemahaman, implementasi, dan pengembangan instrumen berbasis HOTS guna menciptakan pembelajaran yang berkualitas.